German industrial policy and the twin transition: Pre- and post-Covid trajectories in the automotive and IT services sectors - Salome Topuria; Helena Gräf (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
The European Union (EU) and Germany were already being confronted with rapidly changing dynamics on the economic, ecological, and technological terrains prior to the Covid-19 crisis. The pandemic however has fully exposed critical global value chain (GVC) dependencies, jeopardising European industries. Yet, while the automotive industry was directly hit and worsened by the GVC distortions, the information technology (IT) services sector increased in value. By employing a historical-institutional and a pre-and post- Covid-19 industrial policy analysis, this article finds that in spite of previous attempts, it was during the height of the pandemic that the implementation of green and digital industrial policy gained significant political support in Germany and the EU. In this context, there is an increased relevance of vertical industrial policy, which is geared towards the 'twin transition', partly altering the primarily horizontal industrial policy framework manifested in the post-Maastricht period.
Keywords: L5; L62; O38; 330; Vertical Industrial Policy; Automotive industry; IT services industry; Covid-19; Geopoliticized Competition; Twin Transition